2017
DOI: 10.4184/asj.2017.11.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Dried Human Platelet-Rich Plasma Retains Activation and Growth Factor Expression after an Eight-Week Preservation Period

Abstract: Study DesignControlled laboratory study.PurposeThis study aimed to evaluate the efficacy of platelet-rich plasma (PRP) stored at room temperature (RT), frozen, or after freeze-drying.Overview of LiteraturePRP enriches tissue repair and regeneration, and is a novel treatment option for musculoskeletal pathologies. However, whether biological activity is preserved during PRP storage remains uncertain.MethodsPRP was prepared from blood of 12 healthy human volunteers (200 mL/person) and stored using three methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…Moreover, the main growth factor levels and cytokines were quantitatively assessed ( Table 2). The values presented in Table 2 are in agreement with previously reported data [19,[29][30][31][32][33]. These previous results demonstrated that different plasma formulations enhance proliferation and migration of fibroblast populations, protect and inhibit TGF-1-induced myofibroblast differentiation, and regulate the metabolic activity of mesenchymal stem cells [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the main growth factor levels and cytokines were quantitatively assessed ( Table 2). The values presented in Table 2 are in agreement with previously reported data [19,[29][30][31][32][33]. These previous results demonstrated that different plasma formulations enhance proliferation and migration of fibroblast populations, protect and inhibit TGF-1-induced myofibroblast differentiation, and regulate the metabolic activity of mesenchymal stem cells [33].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the concept of PRGF and its related mechanism is that by increasing the concentration of growth factors and cytokines that are released by platelets, the healing process is accelerated [28]. The actual definition of protein rich plasma (PRP) (and related PRGF) is accepted as a minimum platelet concentration three times that of whole blood [18,19,29]. In our study, as presented in Table 1, the counted platelets are in agreement with this definition.…”
Section: Discussionsupporting
confidence: 77%
“…In conclusion, we showed that PDGF in FD-PRP is pharmacologically active in vitro after 4 weeks of storage. As concluded in previous reports [12,13], for the clinical application of FD-PRP after extended long-term storage, further investigations are required to determine the effects of FD-PRP on human bone fusion and soft tissue repair. If FD-PRP is shown to be clinically applicable, it could be useful to promote bone fusion after bone fracture surgical repair, induce interbody fusion, and provide the appropriate scaffolding for bone formation after spinal surgery without the need of intraoperative blood collection.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, patients are required to donate a large amount of blood just before surgery for fresh PRP preparation. To overcome this limitation, we focused on freeze-dried PRP (FD-PRP) and confirmed that FD-PRP maintained baseline levels of GFs for the entire 8-week duration [12]. Furthermore, Shiga et al [13] showed that FD-PRP could achieve accelerated bone union in a rat PLF model even after 8-week storage.…”
Section: Introductionmentioning
confidence: 96%
“…Typically, PDGF, TGF, epidermal growth factor (EGF) and VEGF are involved in tissue repair and assessed in fresh versus FD-PRP. For example, Shiga et al [17] compared fresh-frozen (−80 ºC) PRP with FD-PRP. They established its stability, up to 8 weeks at room temperature, based on the quantification of PDGF, VEGF, TGF and EGF.…”
Section: Lyophilized Prp Preservationmentioning
confidence: 99%